1998
DOI: 10.1074/jbc.273.13.7390
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Hepatitis C Virus Helicase-associated ATPase Activity by the Combination of ADP, NaF, MgCl2, and Poly(rU)

Abstract: Hepatitis C virus (HCV) helicase has an intrinsic ATPase activity and a nucleic acid (poly(rU))-stimulated ATPase activity. The poly(rU)-stimulated ATPase activity was inhibited by F؊ in a time-dependent manner during ATP hydrolysis. Inhibition was the result of trapping an enzyme-bound ADP-poly(rU) ternary complex generated during the catalytic cycle and was not the result of generating enzyme-free ADP that subsequently inhibited the enzyme. However, catalysis was not required for efficient inhibition by F ؊ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
1
31
1
Order By: Relevance
“…This is in contrast with a report that proposes that the HCV helicase monomer has two ATP binding sites (10). The stoichiometry of 1:1 in our studies was obtained by direct equilibrium binding measurements, whereas the reported studies used the inhibition of ATPase activity as a function of ADP concentration in the presence of NaF to obtain the 1:2 stoichiometry.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…This is in contrast with a report that proposes that the HCV helicase monomer has two ATP binding sites (10). The stoichiometry of 1:1 in our studies was obtained by direct equilibrium binding measurements, whereas the reported studies used the inhibition of ATPase activity as a function of ADP concentration in the presence of NaF to obtain the 1:2 stoichiometry.…”
Section: Discussioncontrasting
confidence: 51%
“…HCV helicase does not form stable oligomers, and each helicase molecule has one nucleic acid binding site (5)(6)(7). Although sequence and crystallographic data support a single NTP binding site (8,9), it was proposed that the HCV helicase molecule has two ATP binding sites (10). In this paper we explore the ATP binding stoichiometry with direct nucleotide binding assays.…”
Section: Scheme Imentioning
confidence: 99%
“…The products of ATP hydrolysis, ADP and P i , do not inhibit the HCV NS3 helicase. However, in the presence of NaF and PolyU RNA, ADP inhibits ATP hydrolysis with about two moles of ADP binding per protein monomer [181]. When beryllium fluoride is added to the reaction, ADP inhibits ATP hydrolysis more potently with a K i of about 8.5 µM [136,146].…”
Section: Sf2 Helicase Inhibitorsmentioning
confidence: 99%
“…Dimerization of NS3 has also been visualized using analytical gel filtration, but only in the presence of an oligonucleotide (Khu et al, 2001). Nucleic acid binding data can sometimes be fit to models that do not take into account subunit interactions (Porter, 1998b;Porter, 1998a;Porter et al, 1998;Levin and Patel, 2002), but under certain conditions, cooperative models fit the data better (Locatelli et al, 2002;Frick et al, 2004b). Taken together, these data suggest that two or more HCV helicase protomers cooperatively assemble onto ssDNA (or RNA) in a controlled manner.…”
Section: Evidence For a Functional Oligomer (The Rolling Model)mentioning
confidence: 89%
“…Porter et al first detected a possible second nucleotide binding site when they studied product inhibition in the presence of NaF. In their studies, about two moles of ADP bound per protein monomer (Porter, 1998a). In contrast, as discussed above, when beryllium fluoride is added to the reaction, only one mole of ADP is bound per protomer (Lam et al, 2003a;Levin et al, 2003).…”
Section: Small Moleculesmentioning
confidence: 99%